1997
DOI: 10.1046/j.1365-2249.1997.3141206.x
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the mechanism by which heparin antagonizes activation of a model endothelium by interferon-gamma (IFN-γ)

Abstract: SUMMARYIFN-g increases the potential immunogenicity of vascular endothelial cells by up-regulation of intercellular adhesion molecule-1 (ICAM-1) and class I MHC antigen expression and by induction of class II MHC antigens and certain chemokines. In this study the mechanism by which the glycosaminoglycan (GAG) heparin antagonizes the activation of a model endothelium by IFN-g was investigated. Radioligand binding assays demonstrated that total binding of 125 I-IFN-g to the EAhy.926 endothelial hybridoma cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 30 publications
0
43
0
Order By: Relevance
“…33,36,37 They also express large amounts of both N-and O-sulfated heparan sulfate on their cell surface as detected by immunofluorescence flow cytometry (data not shown) and have been used previously by this group and others to model endothelial/cytokine interactions. [38][39][40] Importantly, immunofluorescence microscopy demonstrated that they lack cell surface expression of CCR2, the cognate receptor for MCP-1 (data not shown).…”
Section: Resultsmentioning
confidence: 95%
“…33,36,37 They also express large amounts of both N-and O-sulfated heparan sulfate on their cell surface as detected by immunofluorescence flow cytometry (data not shown) and have been used previously by this group and others to model endothelial/cytokine interactions. [38][39][40] Importantly, immunofluorescence microscopy demonstrated that they lack cell surface expression of CCR2, the cognate receptor for MCP-1 (data not shown).…”
Section: Resultsmentioning
confidence: 95%
“…A large body of work has been carried out in this area, and blocking interactions between IFN-g and endothelial GAGs was suggested as a clinical method of immunosuppression (66), whereas mutation of the GAG binding site of RANTES has revealed a novel anti-inflammatory strategy (67). Moreover, anti-inflammatory properties of a cationic-derived peptide of mouse IFN-g was shown to inhibit the GAG binding capacity of IL-8 (68).…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing endothelial cell layers and immobilized purified GAGs, others have shown that human IFN-␥ binds to heparin, heparan sulfate, and chondroitin sulfate, sulfation of the GAGs being essential for in this interaction (12)(13)(14)(15)(16)39). Binding is thought to be an ionic interaction between positively charged basic amino acids near the C terminus of IFN-␥ and the negatively charged sugar residues on GAGs (16).…”
Section: Discussionmentioning
confidence: 99%
“…One possible candidate is cell surface proteoglycans. In common with other cytokines and growth factors, human IFN-␥ has been shown to bind to proteoglycans of the extracellular matrix, and more specifically to the glycosaminoglycans (GAGs) heparin, heparan sulfate, and chondroitin sulfate (12)(13)(14)(15)(16). The binding interaction between human IFN-␥ and heparan sulfate has been well characterized: it involves two groups of carboxyl-terminal basic amino acids on the cytokine and two sulfated domains of heparan sulfate, such that the two domains of the GAG directly bind the two carboxyl-terminals of an IFN-␥ dimer (13,(17)(18)(19).…”
mentioning
confidence: 99%